Edison Electronics Ltd.’s business strategy changes, single brand showroom to multi-brand showroom. (Financial point of view) - Razib, Mohammad Kamrul Hasan (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Masters of Business Administration, 2018.